Equity and Technology Use in Education - Masmali, Abdullah (Advances in Social Sciences Research Journal, 2020)
With the rapid adoption of technology in the education sector, a paradigm shift from traditional learning methods to digital learning has been experienced. This article focuses on the importance of ensuring equity in the use of technology among learners, as it relates to their right to access educational technology. While the issue of digital transformation in education is a shared responsibility among educators, this article discusses it from a comprehensive perspective. Supposedly, equity in educational technology access is an issue addressed by researchers in different school settings, including researchers in science in K-12 settings. This article describes how assessment and evaluation could make a difference among learners when it comes to enhancing their capacity to access and use technology in learning. The article concludes with some recommendations for educational technology policymakers to ensure that all students have the same opportunity in accessing educational technology in a bid to avoid a digital divide among learners.